The great railroad race : the diary of Libby West - Gregory, Kristiana (New York : Scholastic, 1999)
As the daughter of a newspaper reporter, fourteen-year-old Libby keeps a diary account of the exciting events surrounding her during the building of the railroad in the West in 1868.
"Utah Territory, 1868"--Cover.
970
Accelerated Reader AR
Keywords: Historical fiction; Frontier and pioneer life -- West (U.S.) -- Fiction; Diaries -- Fiction; Railroads -- Juvenile fiction; West (U.S.) -- Fiction